The Prevalence, Intensity and Degree of Infestation Profile Argulus japonicus Ectoparasite in Common Carp (Cyprinus carpio) at Ngawi and Tambakrejo, Sidoarjo, East Java, Indonesia - Bahtiar, Sadida Anindya; Kismiyati; Nirattisai Petchsupa (Department of Aquaculture, 2024)
The demand for common carp in Indonesia is high, and the success of seed production relies on the quality of the broodstock. However, freshwater aquaculture faces challenges from diseases, particularly parasites like Argulus japonicus. This study aimed to determine the prevalence, intensity, and degree of infestation of A. japonicus on common carp. The research method was survey. The research was conducted in October 2019 at Ngawi Fish Hatchery Center and in November 2023 at Tambakrejo Village, Waru, Sidoarjo, East Java, Indonesia. There were 26 broodstock of common carp as samples. A. japonicus were ectoparasites found to infest 10 common carp (Cyprinus carpio) broodstock that were ready to spawn at Fish Hatchery Center in Ngawi, East Java and 16 common carp (C. carpio) that raised from Tambakrejo Village farmer in Waru, Sidoarjo, East Java. Prevalence of the fish infested with A. japonicus was same in 100% at both regions. However, there is different in the intensity of A. japonicus at Ngawi Fish Hatchery Center (29 individuals/head) and at Tambakrejo Village, Waru, Sidoarjo (42,5 individuals/head). But, the degree of infestation in both location was classified as severe. Attachment site of A. japonicus were in the fish body surface, fins, and mouth. During the research, water quality is in normal limits that can be observed by 28°C temperature, 7.1 pH, and 2.6 mg/L DO. In conclusion, common carp in Ngawi Fish Hatchery Center and Tambakrejo Village, Waru, Sidoarjo, East Java, were infested with the heavy category of A. japonicus.